Direct Determination of Geomagnetic Baselines During Quiet Periods for Low‐ and Mid‐Latitude Observatories. Issue 8 (13th August 2022) - Haberle, V.; Marchaudon, A.; Chambodut, A.; Blelly, P.‐L.
Abstract: The geomagnetic field is composed of a variety of sources that act on a wide range of timescales and amplitudes. The separation of magnetic storm effects from quiet variations is needed to accurately quantify impacts of space weather events. The extraction of such quiet contributions within geomagnetic measurements is achieved by the determination of baselines, which, ideally, is done by a simple algorithm which captures quiet sources suitably well, while being applicable to an extensive network of magnetic observatories independent of the period of time. In this work, we apply signal filtering techniques on the horizontal components of geomagnetic field measurements from low‐ and mid‐latitude observatories to determine baselines. The variations within the baseline are investigated for magnetically quiet periods between 1991 and 2019, focusing on long‐term trends, seasonal and local time dependencies, and day‐to‐day variability. The analysis confirms that the contributing quiet sources include the secular variation and the solar quiet (Sq) current system. The non‐negligible day‐to‐day variability, that is typical for Sq in low‐ and mid‐latitudes, is embedded within the baseline. Thus, the filter approach extracts quiet magnetic field variations well. Comparisons with other baseline methods show good agreements. We conclude that the filter approach can be used to determine baselines automatically during magnetically quiet periods without the need of further apriori information and is applicable on a wide network of magnetic observatories. It marks the first step for deriving magnetic indices for (near) real‐time space weather applications. Plain Language Summary: The Earth's intrinsic magnetic field is generated by the motion of molten rock within its interior and interacts with the constant flow of charged particles coming from the Sun. Measurements of the geomagnetic field strength on the surface not only include the intrinsic magnetic field but also phenomena that arise due to this interaction. Some of these phenomena show regular variations without major effects and some, like solar storms, are able to disrupt the geomagnetic field, affecting technological systems. In order to quantify how harmful disruptive events are, it is important to determine the regular variations first. In this paper, we determine the regular variations within the signal (baselines) by applying signal filtering techniques on geomagnetic field measurements. Our analysis shows that regular variations during undisturbed days in low‐ and mid‐latitude ranges are captured accurately. Key Points: A basic signal filtering approach is used to determine geomagnetic baselines during quiet periods The baselines capture the secular variation and solar quiet current systems accurately The baseline method is applicable for low‐ and mid‐latitude magnetic observatories and does not require any apriori information